Novel Innovations in Herbal Wine and Pharmacological Potential - Dwi Rahayu Pujiastuti; Mario Nikolaus Dalengkade (JURNAL BIOS LOGOS, 2025)
In recent years, the wine industry has undertaken various innovations to support the development of functional foods, as evidenced by numerous wine products formulated with herbal plants. These combinations have resulted in a diversity of secondary metabolites, which are of significant interest to the pharmaceutical industry. Nevertheless, further breakthroughs are needed to introduce novelty in herbal wine products. One such innovation involves the utilization of Cymbopogon citratus, Zingiber officinale, Citrus hystrix, Elettaria cardamomum, Cinnamomum verum, Syzygium aromaticum, and Caesalpinia sappan L. This study identified 85 compounds, demonstrating distinct differences in the chemical of bioactive compounds between the raw herbal plants and the fermented product. These differences are attributed to substitution reactions occurring in the carbon framework, resulting in the formation of derivative compounds in the herbal wine. Additionally, enzymatic reactions mediated by Saccharomyces cerevisiae during fermentation led to the formation of biologically important precursors, such as N-Acetylmannosamine, which plays a role in the regulation of GNE gene mutations. Therefore, the herbal wine produced in this study presents potential as a functional food with promising pharmacological applications.